(untitled) (Research, Society and Development, 2024)
The objective of this study is to investigate the effects of mangiferin and its by-products on the prevention and treatment of chronic non-communicable diseases (NCDs) through a bibliographic review of narrative literature, addressing the bioactive compounds found in mango leaves (Mangifera indica L.) and the relationship between its consumption and NCD prevention. The research was carried out from January 2024 to March 2024 in the online databases Scientific Electronic Library Online - SciELO, National Library of Medicine (PubMed) and Biblioteca Virtual em Saúde (VHL), whose publication period falls between 2018 and 2024, in English, available and complete texts. The exclusion criteria were works that were not in this publication period, were unrelated to the theme or were duplicates. The first stage consisted of selecting relevant studies, for which we carried out a search in the databases, selecting titles that deal with the desired topic and using the corresponding descriptors. In the second stage, we analyzed the titles and abstracts of the articles, forwarding those that aligned with the topic addressed to the next stage. In the third stage, we read the documents in full, highlighting the relevant parts related to the subject covered in this work.